EKSTRAKSI DAN KARAKTERISASI MINYAK ATSIRI DARI DAUN LIMAU KUIT DENGAN METODE DISTILASI UAP–AIR DAN KONDENSOR BOLA TERMODIFIKASI SERTA ANALISIS KOMPOSISINYA MENGGUNAKAN GC-MS - Veronika Lasmaida Panjaitan; Azidi Irwan (Universitas Lambung Mangkurat, 2023)
Limau kuit is a typical orange from South Kalimantan which is used by the Banjar people in some certain local culinary. This experiment is explorative research that aims to determine the yield of essential oils obtained by hydrosteam distillation method with ball condenser (type of Allihn) cooling, to determine the characterization of the oil comprising specific gravity, refractive index, optical ratation, solubility in alcohol, the composition of using GC-MS. The leaves of limau kuit were air-dried for one week to decrease the water content and then were cut into smaller pieces about 5 mm in size. A 2.050 grams of the sample lay into the tray of the distillation kettle which was filled with adequate water. The distillation was carried out for about 6 hours and 50-60oC in temperature. The results showed that the performed extraction yielded 0.59%-(v/w) or 0.52%-(w/w) of oils. The oil values of specifie graviry, refractive index, optical ratation, and solubility in alcohol 90% were 0.8285, 1.472, (-)1.90, and 1:4 respectively. The CG-MS analysis showed 31 chemical compounds of the oils and these were five the dominants: γ-terpinene (24,19%), followed by prehnitene (18,26%), (+)-4-carene (8,53%), β-cis-ocymene (7,20%), and β-pinene (5,46%) respectively.